A CIÊNCIA NA MÍDIA E NA ESCOLA - Grillo, Sheila Vieira de Camargo (Intercâmbio, 2010)
Comparative approache to discoursive aspects in scientific popularization and in Biology textbooks, through Bakhtin’s concepts of comunicational sphere, verbal interaction and genres of discourse.